2013
DOI: 10.1186/1471-2229-13-13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the basal angiosperm Aristolochia fimbriata: a potential experimental system for genetic studies

Abstract: BackgroundPrevious studies in basal angiosperms have provided insight into the diversity within the angiosperm lineage and helped to polarize analyses of flowering plant evolution. However, there is still not an experimental system for genetic studies among basal angiosperms to facilitate comparative studies and functional investigation. It would be desirable to identify a basal angiosperm experimental system that possesses many of the features found in existing plant model systems (e.g., Arabidopsis and Oryza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 101 publications
(126 reference statements)
0
21
0
Order By: Relevance
“…Among magnoliids, Aristolochia fimbriata (pipevine; Aristolochiaceae) has been proposed as a potential experimental system and has numerous features that facilitate genetic studies ( Bliss et al 2013 ). Whereas most magnoliids are woody, this species is herbaceous, easily cultured with a rapid life cycle (3 months), transformable, and can be regenerated via tissue culture.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Among magnoliids, Aristolochia fimbriata (pipevine; Aristolochiaceae) has been proposed as a potential experimental system and has numerous features that facilitate genetic studies ( Bliss et al 2013 ). Whereas most magnoliids are woody, this species is herbaceous, easily cultured with a rapid life cycle (3 months), transformable, and can be regenerated via tissue culture.…”
Section: Moving Forwardmentioning
confidence: 99%
“…The present research aims to assess the genetic basis responsible for the petaloid perianth and the gynostemium identity in Aristolochia , having the ABCE model as a reference point ( Figure 1 ). In order to do so we have selected Aristolochia fimbriata Cham., as this species has recently been proposed as a candidate magnoliid for evolutionary developmental studies for being a self-compatible herb with continuous flowering, and having high rate of seed germination, small genome size, and low (2 n = 14) chromosome number ( Bliss et al, 2013 ). The species is native to temperate South America but has been widely spread as an ornamental.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the monophyly of Pararistolochia was confirmed by molecular-based phylogenetic analyses (Neinhuis et al 2005. Ohi-Toma et al (2006) and Bliss et al (2013) showed that the Australasian and African species belonging to Pararistolochia are sister groups. On the basis of morphological synapomorphies, both subgeneric and generic rank would be acceptable for Pararistolochia.…”
Section: Taxonomic Historymentioning
confidence: 94%
“…Hutchinson and Dalziel (1927) first described the genus Pararistolochia, exclusively containing African species. Both morphological (Huber 1960(Huber , 1985González and Stevenson 2002) and molecular phylogenetic studies (Ohi-Toma et al 2006;Bliss et al 2013) have shown that Pararistolochia occurs not only in Africa, but that species from Australasia have to be included as well. Aristolochiaceae are important host plants for various genera of the family Papilionidae (Lepidoptera) (Simonsen et al 2010).…”
Section: Introductionmentioning
confidence: 99%